2021
DOI: 10.1038/s41598-021-84532-y
|View full text |Cite
|
Sign up to set email alerts
|

18S rRNA gene sequences of leptocephalus gut contents, particulate organic matter, and biological oceanographic conditions in the western North Pacific

Abstract: Eel larvae apparently feed on marine snow, but many aspects of their feeding ecology remain unknown. The eukaryotic 18S rRNA gene sequence compositions in the gut contents of four taxa of anguilliform eel larvae were compared with the sequence compositions of vertically sampled seawater particulate organic matter (POM) in the oligotrophic western North Pacific Ocean. Both gut contents and POM were mainly composed of dinoflagellates as well as other phytoplankton (cryptophytes and diatoms) and zooplankton (cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…The recent results of eukaryotic 18S rRNA gene sequence compositions based on metabarcoding technique also showed Dinophyceae are dominant >75% of eukaryotic community in the western NPSG [39]. The metabarcoding results [39] were consistent with our microscopic observations, with the exception of Dinophyceae which comprised a larger proportion of the community in metabarcoding results. This is likely due to Dinophyceae having larger nuclear genome sizes compared to other microplankton [40].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…The recent results of eukaryotic 18S rRNA gene sequence compositions based on metabarcoding technique also showed Dinophyceae are dominant >75% of eukaryotic community in the western NPSG [39]. The metabarcoding results [39] were consistent with our microscopic observations, with the exception of Dinophyceae which comprised a larger proportion of the community in metabarcoding results. This is likely due to Dinophyceae having larger nuclear genome sizes compared to other microplankton [40].…”
Section: Plos Onesupporting
confidence: 89%
“…This is likely due to Dinophyceae having larger nuclear genome sizes compared to other microplankton [40]. In addition, the contribution of other flagellates was remained very low in the metabarcoding technique results [39]. This observation suggests that while microscopic observation is a time consuming technique, it is still a necessary tool to understand the micro-size plankton community in the oligotrophic ocean; furthermore, this indicates that the metabarcoding technique should best be coupled with more traditional methods such as microscopic observations.…”
Section: Plos Onementioning
confidence: 98%
“…Speculation on the feeding habits of eel leptocephali in nature varies (Miller et al ., 2011; Mochioka and Iwamizu, 1996; Otake et al ., 1993; Riemann et al ., 2010; Terahara et al ., 2011). Recently, particulate organic matter (POM) in the ocean surface layer (Feunteun et al ., 2015; Miller et al ., 2013; Tomoda et al ., 2018; Watanabe et al ., 2021) comprising natural materials, zooplankton carcasses and dead phytoplankton ( e.g ., marine snow) has been described as a main food. Nonetheless, the actual materials that leptocephali feed on in situ , and the distribution of these in time and space in sea water, are mostly undetermined; thus the feeding ecology and dietary preferences of anguilliform leptocephali are still poorly understood (Chow et al ., 2019a; Ghinter et al ., 2020; Miller et al ., 2020; Tsukamoto & Miller, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The cyanobacterial picoplankton Synechococcus spp. exists as suspended particles in sea water in areas inhabited by A. japonica leptocephali (Ayala et al ., 2018; Buitenhuis et al ., 2012; Flombaum et al ., 2013; Watanabe et al ., 2021). The main aim of this study is to better understand the general feeding ecology of eel larvae.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-size plankton is not the major primary producers of the western NPSG, but they are one of the key groups in the ecosystems linked to the higher trophic organisms. Watanabe et al [39] reported the direct importance of micro-size plankton for the larval eels growing up in the western NPSG. The other important role of the micro-size plankton of this area is the size-up of organic matter.…”
Section: Plos Onementioning
confidence: 99%